Keeping my professional development continuous - Wanjiku Mathenge (Community Eye Health Journal, 2017)
Keeping up professionally means knowing what is current and then selecting what is applicable to your work. This requires a personal commitment to recognise the need, find the time and seek resources. The process is lifelong and can become part of your routine.